Biocultural Potential of Multifunctional Flora in Urban Green Open Spaces: A Case Study of Tabebuya Park, South Jakarta - Kun Mardiwati Rahayu; Andikha Bima Prasetyo; Ribath Ridwanulloh (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to identify the composition of flora species in Tabebuya Park, analyze the biocultural potential of its flora, and explain its implications for strengthening the ecological, social, and cultural functions of urban green open spaces. The main issue underlying this study is the lack of integrated information on species composition and the biocultural use potential of flora in urban parks as a basis for urban green space management. The study employed an exploratory approach using the cruise method through direct inventory of all vegetation at the study site. Species identification was conducted based on morphological observations, visual documentation, and the use of an artificial intelligence (AI)-based plant identification application as a preliminary tool, which was subsequently verified using botanical literature and taxonomic references. Data were analyzed descriptively and quantitatively by calculating relative frequency and grouping plants according to ethnobotanical use categories derived from the literature. The results showed that Tabebuya Park contains 53 plant species from 34 families, with high multifunctional potential, including 42 medicinal species, 31 ornamental plants, 9 aromatic plants, 2 dye-producing plants, 21 food and beverage plants, 5 culinary spice plants, 20 cosmetic plants, and 10 plants used for rituals or customary practices. These findings confirm that Tabebuya Park functions not only as an aesthetic element of the urban landscape, but also as a biocultural green space that plays an important role in providing ecosystem services, supporting educational activities, and improving the quality of life of urban communities.